Performance Measures Predict the Onset of Basic ADL Difficulty in Community-Dwelling Older Adults - Huang, Wen-Ni Wennie (2010)
OBJECTIVES: To assess the predictive value of five performance-based measures for the onset of difficulty in basic activities of daily living (ADL). DESIGN: A prospective cohort study; home visits every 6 months for 18 months. SETTING: Community-based PARTICIPANTS: Community-dwelling older adults, n=110, (mean age, 80; SD, 7.0; range, 67-98 years) who reported no difficulty in basic ADLs. MEASUREMENTS: The Short Physical Performance Battery (SPPB), gait speed, Berg Balance Scale (BBS), grip strength, and Timed Up & Go Test (TUG) were evaluated at baseline. Seven ADL items were assessed at baseline, 6, 12 and 18 months. The onset of basic ADL disability was self-report of difficulty in any of the 7 ADL items. Logistic regression models were fitted for each of the physical performance measures to predict onset of basic ADL difficulty at 6, 12, and 18 months. RESULTS: After controlling for age, co-morbid conditions, and gender, the BBS was the most consistent and best predictor for the onset of basic ADL difficulty over an 18-month period (6 months, c-statistic=.725 (.60, .85); 12 months, c-statistic=.840 (.75, .93); 18 months, c-statistic=.821 (.71, .93)). The SPPB showed excellent predictive value for the onset of difficulty at 12 months. The number of older adults completed the 6, 12, and 18-month follow-up visits were 95, 89, and 75, respectively. CONCLUSION: BBS, followed by SPPB, TUG, gait speed and grip strength were predictive for the onset of basic ADL difficulty over an 18-month period in community-dwelling older adults. Screening nondisabled older adults with simple performance tests could allow clinicians to identify those at risk for ADL difficulty, and may help to detect early functional decline.